IMPLEMENTASI KEBIJAKAN PROGRAM DESA FOKUS DI DESA NEKAN KECAMATAN ENTIKONG KABUPATEN SANGGAU - Mona E.42008018, Martha (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of the research is "The Policy Implementation of Focus Village Program in theNekan Village in the district of Entikong, Region of Sanggau". This reseach is intended to producea relevant recommendation about The Policy Implementation of Focus Village Program in theRegion of Sanggau, especially in the Nekan Village, in the district of Entikong which is located inborder territory.The title of this thesis raised based on the phenomenon of the implementation of the policyat the focus Village Program in the Nekan village,the District of Entikong which is indicated that ithas not fully able to bring the positive contribution to the progress, prosperity and improving thequality of human resources in the nekan village as the original purpose of the program.According to these problems, this research use qualitative research types, with descriptivemethods. The Subjects in this research are the government and the people involved in theimplementation of the policy at the focus Village Program in the Nekan village. And the data thatrelated to the object of the research was obtained by the three techniques of data collection, theinterview technique, observation, and documentation.The conclusion of this research is, there are still programs that implemented by governmenttrough the policy of focus village that is not proper yet to the needs of rural communities so that ithas not implemented to the maximum, and there is a work program that has not been up that iscaused by several factors such as the allocation of time and financial issues, as well as the policyintern organizers issues, particularly those involving to the education and infrastructure thatbecome the focus of this research.Â Keywords: Policy Implementation Processes, Infrastructure, and Education